Gain-switched seed laser for Deep Space communication applications - Grześ, Paweł; Michalska, Maria; Świderski, Jacek (Photonics Letters of Poland, 2018)
Deep Space (DS) communication plays an important role in space exploration programs, especially in interplanetary flights projects. To resolve limitations of a well-known microwave link, an optical communication is considered. In the article a gain-switched seed laser for high power transmitter in a Master Oscillator Power Amplifier (MOPA) architecture is presented. This optical signal source is able to generate picosecond pulses on demand and is suitable for high speed data link over a long range. The laser is dedicated to the pulse position modulation (PPM) scheme for low power consuming, high capacity and energy efficient optical communication. Full Text: PDF References H. Hemmati, Deep Space Optical Communications (Jet Propulsion Laboratory 2005), John Wiley & Sons, 2006. CrossRef T. Tolker-Nielsen and G. Oppenhauser, “In-Orbit Test Result of an Operational Intersatellite Link between ARTEMIS and SPOT 4,” FreeSpace Laser Communication Technologies XIV, Proceedings of SPIE, vol. 4639, pp. 1–15, San Jose, California, January 2002. CrossRef D. M. Boroson, et al., "Overview and results of the Lunar Laser Communication Demonstration", Proc SPIE 8971, 89710S (2014). CrossRef D. M. Boroson, A. Biswas, B. L. Edwards, "MLCD: overview of NASA's Mars laser communications demonstration system", P. Soc. Photo-Opt. Ins. 5338 (2004). CrossRef H. Hemmati, A. Biswas, I. B. Djordjevic, "Deep-Space Optical Communications: Future Perspectives and Applications", Proc. of the IEEE 99.11, (2011). CrossRef H. Kaushal, G. Kaddoum, "Optical Communication in Space: Challenges and Mitigation Techniques", IEEE Commun Surv Tut. 19.1, 57 (2017). CrossRef B. Moision, J. Hamkins, M. Cheng, "Deep-space optical communications downlink budget: modulation and coding", IPN Prog. Rep. 42.154, 1 (2005). DirectLink